The Treatment of IgA Nephropathy - Lai, Kar Neng (Kidney Dis (Basel), 2015)
BACKGROUND: IgA nephropathy (IgAN) is a very common glomerulonephritis worldwide. Nevertheless, treatment options for primary IgAN are still largely based on opinion or weak evidence. There is a lack of large randomized controlled trials (RCT) that provide a definitive immunosuppressive protocol for IgAN. The recent KDIGO Clinical Practice Guidelines for Glomerulonephritis have assigned low levels of evidence for almost all recommendations and suggestions related to this nephropathy. SUMMARY: In this article, we review different treatment options and emphasize that the key to therapeutic decision-making is the assessment of an individual's prognosis. The risk of disease progression is closely related to clinical parameters such as proteinuria, hypertension, and impaired glomerular filtration rate. For patients with minor urinary abnormalities, the mainstay of treatment is long-term regular follow-up to detect renal progression and hypertension. Optimized supportive care aiming to maintain proteinuria <1 g/day is preferred in the typical patient presenting with microhematuria, significant but nonnephrotic proteinuria, hypertension, and variable degrees of renal failure. The atypical patient with overt nephritic syndrome or rapidly progressive kidney injury that represents a vasculitic form of IgAN should be treated with immunosuppression. Finally, the variant of overlapping syndrome of IgAN and lipoid nephrosis that runs a good prognosis should be treated as lipoid nephrosis. KEY MESSAGE: The treatment of IgAN should be structured according to the clinical scenario.